Strengthening the foundations and bases during reconstruction and application hidroplyty in difficult ground conditions - Євдокименко, А.В.; Барабаш, М.С. (Proceedings of National Aviation University, 2007)
The article is devoted to the questions of strengthening of foundations during reconstruction of buildings with arrangement of underground parking in the difficult ground conditions.